The waters : a novel [large type] - Campbell, Bonnie Jo, 1962- (Thorndike Press large print top shelf., 2024)
"On an island in the Great Massasauga Swamp--an area known as "The Waters" to the residents of nearby Whiteheart, Michigan--herbalist and eccentric Hermine "Herself" Zook has healed the local women of their ailments for generations. As stubborn as her tonics are powerful, Herself inspires reverence and fear in the people of Whiteheart, and even in her own three estranged daughters. The youngest--the beautiful, inscrutable, and lazy Rose Thorn--has left her own daughter, eleven-year-old Dorothy "Donkey" Zook, to grow up wild. Donkey spends her days searching for truths in the lush landscape and in her math books, waiting for her wayward mother and longing for a father, unaware that family secrets, passionate love, and violent men will flood through the swamp and upend her idyllic childhood. Rage simmers below the surface of this divided community, and those on both sides of the divide have closed their doors against the enemy. The only bridge across the waters is Rose Thorn. With a "ruthless and precise eye for the details of the physical world" (Jane Smiley, New York Times Book Review), Bonnie Jo Campbell presents an elegant antidote to the dark side of masculinity, celebrating the resilience of nature and the brutality and sweetness of rural life"--